Ex Vivo Comparison of 7 Polydioxanone, 2 Polyglactin 910 for Closure of Ventral Median Celiotomy in Horses1. Issue 4 (22nd February 2013) - Anderson, Stacy L.; Bracamonte, José L.; Hendrick, Steve; Carmalt, James L.; Wilson, David G.
Abstract Objective To compare bursting strength and failure mode between ventral median celiotomies closed with USP 7 braided polydioxanone (7PD) or USP 2 polyglactin 910 (2PG). Study Design Ex vivo experimental. Animals Equine cadavers (n = 10). Methods A 25 cm ventral median celiotomy was created in fresh equine cadavers. A 200 L polyurethane bladder was inserted into the abdomen. Celiotomies were closed in a simple continuous pattern with 2 sections of 7PD or 2PG. The bladder was inflated with compressed air until construct failure. The horses' signalment, body weight, suture type, failure mode (suture or abdominal wall), and bursting strength (mmHg) were recorded. Interactions between independent and dependent variables were assessed with statistical tests including linear regression. Results Failure mode was significantly different by suture type (P = .01). Four of 5 celiotomies closed with 2PG failed at the suture; whereas, 0 celiotomies closed with 7PD failed at the suture. In celiotomies closed with 7PD, increasing age was highly and negatively correlated with bursting strength (r = −0.99). When the effect of age was controlled, 7PD had a significantly higher bursting strength than 2PG (P = .024). Conclusion 7PD has a higher bursting strength compared with 2PG. Suture failure was the main failure mode for 2PG; whereas, all celiotomies closed with 7PD failed at the abdominal wall.